Developing Authentic Problems through Lived Experiences in Nature - GÜREL, ZEYNEP (AMER INST PHYSICS, 2017)
This study's main objective is to develop a theoretical and ontological basis for experimentation in contact with the real life, oriented to physics education. Physics is built upon the observation of nature, where our experience provides opportunity to deal with science in natural environment to those learners who have background in the very basics and essentials of physics. Physics in Nature course includes visiting and camping experiences situated in nature and organizing camp with educational purposes. The course has been integrated with indoor and outdoor settings interactively and the authentic problems, which have been taken from outdoor settings, have been brought into the class without well-defined structure (Ill-structured problems). Within the period of ten years, there were plethora of events and problems that would provide sufficient material for many researchers. Because every problem is an event and has a story. The philosophical event concept of Deleuze and Guattari has been used in the events of Physics in Nature courses. Post-qualitative research methodology has been used in order to put forward how to construct the relation between physics and nature and become the main problem in the physics in nature, thereby it has been the basis of the course and our academic research